Survey of Traffic Volume Forecasting - Pawar, Aditi R; Aote, Shailendra S (International Journal of Computer Sciences and Engineering, 2025)
The trafﬁc ﬂow forecasting is a very important aspect of trafﬁc predication and congestion, it alleviates the increasing congestion problems that cause drivers to save a longer traveling time and economical loses, thus, it is one of the severe problems in big city areas. In tunnels the forecasting may help scheduling the ventilation fans. This way, the cost might be decreased while the air quality increased. The aspect of trafﬁc prediction is that it may give the drivers to plan their travelling time and traveling the path, as they have the predictive data information. In this paper, the survey of different types used for trafﬁc forecasting, the data for these techniques, the output provided by them and analysis insights is provided.